2002
DOI: 10.1016/s0022-5347(05)64727-1
|View full text |Cite
|
Sign up to set email alerts
|

Histological Findings After Colocystoplasty And Gastrocystoplasty

Abstract: Periodic prospective biopsy evaluation of children who have undergone either colocystoplasty or gastrocystoplasty failed to reveal any histological evidence of malignancy after 10-year followup. However, histological evidence of a premalignant lesion 13 years after followup suggests that screening for premalignant lesions should be initiated no later than 6 to 10 years following enterocystoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 19 publications
2
19
1
2
Order By: Relevance
“…Neither the present animal study nor our earlier studies in human material were able to demonstrate changes for malignancy or premalignant alterations after gastrocystoplasty [18]. Close et al [10] found transitional cell hyperplasia and metaplasia but no malignancy or DNA abnormalities in rats using flow cytometry after gastrocystoplasty at 21 to 27 months of follow-up.…”
Section: Discussioncontrasting
confidence: 80%
“…Neither the present animal study nor our earlier studies in human material were able to demonstrate changes for malignancy or premalignant alterations after gastrocystoplasty [18]. Close et al [10] found transitional cell hyperplasia and metaplasia but no malignancy or DNA abnormalities in rats using flow cytometry after gastrocystoplasty at 21 to 27 months of follow-up.…”
Section: Discussioncontrasting
confidence: 80%
“…These vary depending on the type of gastro-intestinal segment used [1][2][3]. Due to the risks of metabolic disturbances and other potential complications, patients need long and continuous followup and care [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately forty percent of these malignancies were reported to be transitional cell carcinomas, suggesting metaplasia in the enteric patch [3]. Experimental animal data [46] and surveillance biopsy data in humans [7] demonstrate that transitional metaplasia is frequently observed in the gastrointestinal segment of bladder augmentations, and this metaplasia may herald the onset of more severe dysplasia and malignancy. Recent analyses of biopsied enterovesicular anastomoses revealed mutations in p53 by restriction site mutation assay in 20% of patients, but found no mutations in the native bladder tissue [8], suggesting a tissue-specific response to the bladder microenvironment.…”
Section: Introductionmentioning
confidence: 99%